Psychological well-being pada mantan narapidana kasus pengguna narkoba - Ayu Dwi Anggraini; Sri Aryanti Kristianingsih (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
Becoming an achiever is not a desire of an individual. Because life in a penitentiary is different from life in society. After serving his sentence, the former prayed hoping to be accepted by society and change for the better. Former difficulties usually experience social pressure unconsciously and find it difficult to overcome them. The purpose of this study is to provide an overview and what factors can influence the state of psychological well-being in former drug users. The subjects of this study were 2 people who were selected by purposive sampling with the characteristics of being able-bodied, male and cases of drug users. This study uses interview and observation methods. The results of this study both subjects have good psychological well-being after leaving prison, this is evident in the results of the discussion that the 6 dimensions of psychological well-being have good value. Then the factors that influence the psychological well-being of the 2 subjects are social support and evaluation of experience.